Pembelajaran Imersif Berbasis Augmented Reality: Sekarang dan Masa Depan - Suzanna Suzanna; Ford Lumban Gaol (Fakultas Ilmu Komputer Universitas Nahdlatul Ulama Sidoarjo, 2021)
This study discusses the use of Augmented Reality (AR) technology in immersive learning seen from its current and future developments. The discussion explores the benefits of AR technology from previous research in the past 5 years. The research method used is qualitative, quantitative, mixed, systems design and review papers by taking a sample of 125 papers which are suitable for the purpose of this study. From the research results, it is known that AR technology will continue to develop into a part of individual and community life. Likewise, in the context of education, AR technology will not only become a set of resources, tools for communicating, collaborating, presenting, creating objects and practices for the teaching process, but AR will become an inseparable part of the world of education.